Anarchism, Modernism, and Nationalism: Futurism's French Connections, 1876–1915. Issue 8 (16th November 2016) - Conversi, Daniele
Abstract: This article examines two of the most significant Italian political movements at the turn of the twentieth century—anarchism and Futurism. Although these movements shared a common vocabulary and rhetoric, they contrasted sharply in their aims and objectives. I address three interrelated questions: How were these movements and their ideologies related to, and perceived by, the ruling elites? What were their mutual influences and inspirational centre? Did both movements share a broader core ideology? To answer these questions, I explore the links, parallels and dissimilarities between anarchism and Futurism in the context of the nationalist mass mobilizations preceding World War I. In line with Emilio Gentile's landmark analysis, I identify the core ideology of Futurism as a potent blend of nationalism and modernism. Futurism's double matrix is thus contrasted with the theory and practice of anarchism, the two displaying sharply differing relationships with political power. I also consider the links between Italian Futurism and French ultra-nationalism as championed by prominent intellectuals, beyond Paris' artistic epicentre, where art and politics intermixed. I conclude that the fusion of modernism and nationalism was central to twentieth-century ideological radicalization to which Futurism fully belonged, but from which anarchism eventually dissociated itself.